Novas fontes de resistência à mosca-minadora Liriomyza sativae (Diptera: agromyzidae) em meloeiro - Celin, Elaine Facco (2016)
The leafminer Liriomyza sativae (Diptera: Agromyzidae) causes serious damage to the melon crop (Cucumis melo L.) in the Northeastern region of Brazil. This region concentras most of the production of this horticultural species for exports. Genetic resistance is one strategies of the integrated management used against this insect pest because its highlighted to be economically viable and environmentally friendly, adding benefits to the grower and consumer. In this context, the objective of this work was to select sources of resistance to leafminer in melon germoplasm and get resistant lines. The experiments were conducted in laboratory and field with and without choice. Fifty-two melon accessions were evaluated using commercial hybrids as a tester. Four new sources of resistance were identified: ‘CNPH 11-1072’ e ‘CNPH 11-1077’, both with lower insect infestation (antixenosis); and ‘CNPH 00-915(R)’ e ‘BAGMEL 56(R)’, by complete mortality of the larvae after the initiation of feeding the mesophyll (antibiosis). Resistant lines were obtained from the respective progenies of each resistance source with antibiosis, by successive selfing, conducted by the pedigree breeding methods. In relation to the resistance for the source ‘BAGMEL 56 (R)’, it was possible to determine the genetic nature of resistance by standard the segregating progenies and through a test cross. It was determined that the resistance was controlled by a dominant gene. The symbol ‘Ls’ was suggested to represent this new identified gene. Moreover, by means of non-preference test with contrasting lines for antibiosis and susceptible hybrid ‘Goldex’, it was shown the presence of antixenosis, in addition to antibiosis, this source of resistance. These types of resistance from ‘BAGMEL 56(R)’ may be associated with different defense mechanisms. It was obtained a resistant line from the ‘CNPH 00-915(R)’ source, but it was not possible to determine the genetic control of this source of resistance. It is necessary to perform a conventional inheritance study using generations P1, P2, F1, F2, RC1 and RC2. Therefore, four sources of resistance were selected and two lines resistant to the leafminer were obtained, which should be used in introgression of these resistances in isolation in advanced lines and, or pyramiding shaped promising hybrid of melon.